Phylogenetic Classification of Feline Immunodeficiency Virus - Biondo, Diezza; Kipper, Diéssy; Gomes Maciel, Jessica; de Oliveira Santana, Weslei; Felipe Streck, André; Ricardo Lunge, Vagner (Acta Scientiae Veterinariae, 2023)
Background: The feline immunodeficiency virus (FIV) is responsible for a retroviral disease that affects domestic and wild cats worldwide, causing Feline Acquired Immunodeficiency Syndrome (FAIDS). FIV is a lentivirus from the family Retroviridae and its genome has 3 main structural genes: gag, pol and env. Phylogenetic studies have classified FIV into 7 subtypes according to the diversity among strains from the World, mainly in the env gene. Epidemiological analyses have demonstrated the high predominance of FIV-A and FIV-B. This in silico study aimed to perform a phylogenetic analysis to study FIV diversity worldwide. Materials, Methods & Results: A total of 60 whole genome sequences (WGS) and 122 FIV env gene sequences were included in 2 datasets, which were aligned using MAFFT version 7. Recombination among genomes and/or env genes was analyzed with RDP5 software. Phylogenetic analyses with both datasets were performed, after removing the recombinant sequences, by the W-IQ-TREE and constructed and edited by the FigTree. A total of 12 recombination events involving 19 WGS were detected. In addition, 27 recombination events involving 49 sequences were observed in the env gene. A high rate of recombinants was observed inter-subtypes (A/B and B/D) and intra-subtypes (A/A). All recombinants were removed from the subsequent phylogenetic analyses. Phylogenies demonstrated 6 distinct main clades, 5 from domestic cats (A, B, C, E, U) and 1 from wild cat sequences (W) in the WGS, as well as in the specific env gene analyses. Most clustered with subtype B sequences. In the WGS analysis, clade B had a prevalence of 65.9% Brazilian sequences (27/41) and 2.4% Japanese sequences (1/41). In the env gene analyses, clade B showed a prevalence of 43.8% of Brazilian sequences (32/73) and 20.5% of USA sequences (15/73). The results of both analyses also confirm the FIV-wide geographical distribution around the world. In the phylogenetic analyses carried out with WGS, sequences from China (1/41; 2.4%), Colombia (1/41; 2.4%) and the USA (1/41; 2.4%) were identified in clade A; sequence from Canada in clade C (1/41; 2.4%); sequence from Botswana belonged to clade E (1/41; 2.4%); sequences from Brazil clustered into clade U (2/41; 5% - data not yet published); and sequences belonging to the clade W were from Canada (1/41; 2.4%) and the USA (5/41; 12.3%). Specific env gene phylogenetic analyses showed sequences from Colombia (1/73; 1.4%), France (2/73; 2.7%), the Netherlands (3/73; 4.1%), Switzerland (2/73; 2.7%), EUA (6/73; 8.3%), belonging to clade A; sequence from Canada belonging to clade C (1/73; 1.4%); sequences from Brazil belonging to clade U (2/73; 5% - data not yet published); and sequences belonging to clade W from the USA (6/73; 8.3%). Discussion: The results presented here demonstrate that FIV has a rapid viral evolution due to recombination and mutation events, more specifically in the env gene, which is highly variable. Currently, this retrovirus is classified into 7 subtypes (A, B, C, D, E, F and U-NZenv) according to their high genomic diversity. It also highlighted the importance of in silico sequence and phylogeny studies to demonstrate evolutionary processes. This was the first study to address the WGS FIV diversity with a phylogenetic approach. Keywords: FIV, in silico, phylogeny, subtypes, recombination.